2023
DOI: 10.1038/s41420-023-01519-6
|View full text |Cite|
|
Sign up to set email alerts
|

Tim-3 protects against cisplatin nephrotoxicity by inhibiting NF-κB-mediated inflammation

Abstract: The impact of Tim-3 (T cell immunoglobulin and mucin domain-containing protein 3) on cisplatin-induced acute kidney injury was investigated in this study. Cisplatin-induced Tim-3 expression in mice kidney tissues and proximal tubule-derived BUMPT cells in a time-dependent manner. Compared with wild-type mice, Tim-3 knockout mice have higher levels of serum creatinine and urea nitrogen, enhanced TUNEL staining signals, more severe 8-OHdG (8-hydroxy-2’ -deoxyguanosine) accumulation, and increased cleavage of cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…3B). NF-κB is an important nuclear transcript factor that induces the expression of various pro-inflammatory cytokines [17]. Therefore, we investigated NF-κB expression during inflammation in cisplatin-induced AKI.…”
Section: Time-restricted Feeding Attenuates the Inflammatory Reaction...mentioning
confidence: 99%
“…3B). NF-κB is an important nuclear transcript factor that induces the expression of various pro-inflammatory cytokines [17]. Therefore, we investigated NF-κB expression during inflammation in cisplatin-induced AKI.…”
Section: Time-restricted Feeding Attenuates the Inflammatory Reaction...mentioning
confidence: 99%
“…TIMs are phosphatidylserine receptors mainly expressed on antigen−presenting cells that are involved in the recognition and efferocytosis of apoptotic cells. They are expressed in immune cells such as NK, T, B, and mast cells and participate in multiple aspects of immune regulation but are also abnormally expressed in cancer cells, contributing to immunosuppression ( 64 , 179 , 180 ). Studies demonstrated that blockade of TIMs improved the anticancer effectiveness of T-cell responses in cancer patients and enhanced the immune cells’ stimulatory properties ( 64 , 180 ).…”
Section: Tam-targeted Therapiesmentioning
confidence: 99%